1984
DOI: 10.1159/000238294
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Parenterally Administered Rifampicin into Bone Tissue

Abstract: This study in 32 patients was undertaken to determine the penetration of rifampicin into bone tissue using the recently developed intravenous formulation of this antibiotic. 300 mg rifampicin given as an intravenous injection over 5 min followed by 300 mg slow intravenous drip infusion over 1 h give a plasma level of rifampicin of more than 2 μg/ml for 6 h. In patients with osteomyelitis, bone rifampicin concentrations ranged from 1.4 to 8.8 μg/gat 2.5–3.5 h after the start of treatment. Osteomyelitis due to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 11 publications
0
13
1
1
Order By: Relevance
“…In child cases, administration of the recommended dose of 10-12 mg/kg/day of rifampicin achieved maximum serum concentrations of 3.3-3.8 pg/ ml [16,26]. In another study, 3 h after intravenous infusion of 600 mg rifampicin, the drug concentrations in the bone reached 1.4-8.8 pg/g [24]. These studies indicate that the range of drug concentrations which occurs clinically in serum and bone overlaps the concentrations of rifampicin which, in the present study, had significant inhibitory effects on osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…In child cases, administration of the recommended dose of 10-12 mg/kg/day of rifampicin achieved maximum serum concentrations of 3.3-3.8 pg/ ml [16,26]. In another study, 3 h after intravenous infusion of 600 mg rifampicin, the drug concentrations in the bone reached 1.4-8.8 pg/g [24]. These studies indicate that the range of drug concentrations which occurs clinically in serum and bone overlaps the concentrations of rifampicin which, in the present study, had significant inhibitory effects on osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…For the following incubation for 20h or 40h at 37°C and 5% CO 2 10 μg/ml tigecyclin, 10 μg/ml gentamicin, 7 μg/ml rifampicin or the combinations tigecyclin/gentamicin or tigecyclin/rifampicin are added. The antibiotic concentrations were chosen according to high level doses that can be reached after intravenous application in serum and tissue [31-33]. Both S .…”
Section: Methodsmentioning
confidence: 99%
“…Several studies shown that after oral administration of rifampicin, the rifampicin concentration in bone and in the joint tuberculosis focus was lower than the effective bactericidal concentration (Roth, 1984;Widmer et al, 1992;Mahajan et al, 1997;Zimmerli et al, 1998;Isefuku et al, 2001). Therefore, the topical application of rifampicin on tuberculosis foci has been considered as an approach worth investigating.…”
Section: Introductionmentioning
confidence: 99%